Educational Games for Teaching the Essentials of Exact Sciences in Brazil: A Ten-Year Systematic Mapping Study - Sousa, Matheus Campos; Seabra, Rodrigo Duarte; Lima, Phyllipe (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento Digital, 2025)
Introduction: Exact science subjects are constantly labeled difficult and are known for causing difficulties for students during the learning process. Educational games are an alternative to complement and improve the teaching process, combining entertainment and pedagogical purposes. Objective: This research presents a ten-year systematic mapping study of scientific articles published in specialized events and journals in Brazil, aiming to identify educational games for teaching the essential bases of exact sciences. Methodology or Steps: The study started with an extensive search of scientific databases, identifying 537 initial publications. After applying selection and exclusion criteria, the final dataset was narrowed down to 86 publications. Results: The main results showed that the content covered is related to teaching mathematics; its availability to the general public is limited, and the predominant genre of games is quizzes using gamification.